The phenomenon of non-psychotic denial of pregnancy in Winnicotian perspective - Gonçalves, Thomás Gomes (Revista de Psicologia da IMED, 2014)
This is a theoretical study which addresses the phenomenon of non psychotic denial of pregnancy which a woman does not know she is pregnant during a significant part of the pregnancy or even until labor. This situation is explored from the Winnicottian perspective addressing aspects related to the maternal psychic condition, especially concerning the concept of primary maternal preoccupation as an essential factor in the relationship between mother and child. Some hypotheses are presented concerning a conflict which unable the mother to recognize her own pregnant condition as well as we discuss about the consequences of this impossibility in the quality of the relationship mother-child.